The SIRT2 Deacetylase Regulates Autoacetylation of p300 - Black, Joshua C. (2008)
Autoacetylation of the p300 histone acetyltransferase controls the transition between VP16-mediated chromatin acetylation and preinitiation complex (PIC) assembly. Currently, it is unknown if and how autoacetylated p300 is deacetylated. We found that the NAD(+)-dependent histone deacetylase SIRT2 deacetylates p300 in vitro and in cells. SIRT2 deacetylates lysine residues in the catalytic domain of p300 and restores binding of p300 to the PIC. RNAi-mediated depletion or chemical inhibition of SIRT2 in cells results in accumulation of acetylated p300. The altered ac-p300/p300 ratio in SIRT2-depleted cells results in decreased p300 recruitment to an integrated VP16-responsive gene and inhibition of transcription. We conclude that p300 undergoes a dynamic cycle of autoacetylation and deacetylation.